Pro-Death Signaling of GRK2 in Cardiac Myocytes after Ischemic Stress Occurs via ERK-Dependent, Hsp90-Mediated Mitochondrial Targeting - Chen, Mai (2013)
RATIONALE: GRK2 is abundantly expressed in the heart and its expression and activity is increased in injured or stressed myocardium. This up-regulation has been shown to be pathological. GRK2 can promote cell death in ischemic myocytes and its inhibition by a peptide comprised of the last 194 amino acids of GRK2 (known as βARKct) is cardioprotective. OBJECTIVE: The aim of this study was to elucidate the signaling mechanism that accounts for the pro-death signaling seen in the presence of elevated GRK2 and the cardioprotection afforded by the βARKct. METHODS AND RESULTS: Using in vivo mouse models of ischemic injury and also cultured myocytes we found that GRK2 localizes to mitochondria providing novel insight into GRK2-dependent pathophysiological signaling mechanisms. Mitochondrial localization of GRK2 in cardiomyocytes was enhanced after ischemic and oxidative stress, events that induced pro-death signaling. Localization of GRK2 to mitochondria was dependent upon phosphorylation at residue Ser670 within its extreme carboxyl-terminus by extracellular signal-regulated kinases (ERKs), resulting in enhanced GRK2 binding to heat shock protein 90 (Hsp90), which chaperoned GRK2 to mitochondria. Mechanistic studies invivo and invitro showed that ERK regulation of the C-tail of GRK2 was an absolute requirement for stress-induced, mitochondrial-dependent pro-death signaling, and blocking this led to cardioprotection. Elevated mitochondrial GRK2 also caused increased Ca(2+)-induced opening of the mitochondrial permeability transition pore, a key step in cellular injury. CONCLUSIONS: We identify GRK2 as a pro-death kinase in the heart acting in a novel manner through mitochondrial localization via ERK regulation.